Oatmeal particle size alters glycemic index but not as a function of gastric emptying rate - Mackie, Alan R.; Bajka, Balazs H.; Rigby, Neil M.; Wilde, Peter J.; Alves-Pereira, Fatima; Mosleth, Ellen F.; Rieder, Anne; Kirkhus, Bente; Salt, Louise J. (American journal of physiology: Gastrointestinal and liver physiology, 2017)
The aim of this study was to determine the extent to which oat particle size in a porridge could alter glucose absorption, gastric emptying, gastrointestinal hormone response, and subjective feelings of appetite and satiety. Porridge was prepared from either oat flakes or oat flour with the same protein, fat, carbohydrate, and mass. These were fed to eight volunteers on separate days in a crossover study, and subjective appetite ratings, gastric contents, and plasma glucose, insulin, and gastrointestinal hormones were determined over a period of 3 h. The flake porridge gave a lower glucose response than the flour porridge, and there were apparent differences in gastric emptying in both the early and late postprandial phases. The appetite ratings showed similar differences between early- and late-phase behavior. The structure of the oat flakes remained sufficiently intact to delay their gastric emptying, leading to a lower glycemic response, even though initial gastric emptying rates were similar for the flake and flour porridge. This highlights the need to take food structure into account when considering relatively simple physiological measures and offering nutritional guidance. NEW & NOTEWORTHY The impact of food structure on glycemic response even in simple foods such as porridge is dependent on both timing of gastric emptying and the composition of what is emptied as well as duodenal starch digestion. Thus structure should be accounted for when considering relatively simple physiological measures and offering nutritional guidance.